Dura mater-associated Creutzfeldt–Jakob disease: experience from surveillance in the UK. Issue 7 (20th April 2006) - Heath, C A; Barker, R A; Esmonde, T F G; Harvey, P; Roberts, R; Trend, P; Head, M W; Smith, C; Bell, J E; Ironside, J W; Will, R G; Knight, R S G
Abstract : Between 1970 and 2003, seven cases of human dura mater-associated Creutzfeldt–Jakob disease (CJD) were identified in the UK. Furthermore, we identified a case of CJD in a porcine dura graft recipient. The mean incubation period of the human dura mater cases was 93 (range 45–177) months. The clinico-pathological features of the cases are described and compared with cases previously reported in the world literature.